TEAM WORK AND ITS IMPLICATIONS ON THE PERFORMANCE OF ORGANISATIONS - CEAUSESCU AURELIAN IONUT (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This work aims to form high-performing teams, which are characterized by high cohesion, performance, confidence, a better ability to solve tasks and problems, to take risks, to act in a creative way, to resolve conflicts, to have better communication between team members. Studying groups is important for managers because the most common element of all organizations is people, and the most common technique for performing work through these people is to divide them into working groups.